Effect of a Long Bout Versus Short Bouts of Walking on Weight Loss During a Weight‐Loss Diet: A Randomized Trial. Issue 4 (9th February 2019) - Madjd, Ameneh; Taylor, Moira A.; Delavari, Alireza; Malekzadeh, Reza; Macdonald, Ian A.; Farshchi, Hamid R.
Abstract : Objective: This study aimed to evaluate the effect of different daily physical activity (PA) frequencies, while maintaining the same daily volume of PA, on weight loss, carbohydrate metabolism, and lipid metabolism in women with overweight or obesity throughout a 24‐week intervention. Methods: During their weight‐loss plan, 65 women (BMI = 27‐35 kg/m 2 ; age = 18‐40 years) who had a sedentary lifestyle were randomly allocated to the following groups: diet plus a long bout of moderate physical activity (LBP) (one 50‐minute bout of moderate‐intensity PA) 6 d/wk or diet plus short bouts of moderate physical activity (SBP) (two 25‐minute bouts of moderate‐intensity PA) 6 d/wk. Anthropometric and blood measurements were taken at baseline and at 24 weeks. Results: Compared with the LBP group, the SBP group had a greater decrease in weight (SBP: −8.08 ± 2.20 kg; LBP: −6.39 ± 2.28 kg; P  = 0.019), BMI (SBP: −3.11 ± 0.87 kg/m 2 ; LBP: −2.47 ± 0.86 kg/m 2 ; P  = 0.027), and waist circumference (SBP: −8.78 ± 2.62 cm; LBP: −5.76 ± 2.03 cm; P  = 0.026). No significant differences were seen in carbohydrate and lipid metabolism characteristics after 24 weeks. Conclusions: PA undertaken in two shorter bouts per day could be more effective for weight loss than PA undertaken in a daily long bout in adult women in a 24‐week weight‐loss program.